2016
DOI: 10.1016/j.renene.2015.06.054
|View full text |Cite
|
Sign up to set email alerts
|

In situ thermal and acoustic performance and environmental impact of the introduction of a shape-stabilized PCM layer for building applications

Abstract: a b s t r a c tEnergy consumption in buildings accounts for up to 34% of total energy demand in developed countries. Thermal energy storage (TES) through phase change materials (PCM) is considered as a promising solution for this energetic problem in buildings. The material used in this paper is an own-developed shape stabilized PCM with a polymeric matrix and 12% paraffin PCM, and it includes a waste from the recycling steel process known as electrical arc furnace dust (EAFD), which provides acoustic insulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…Several studies are focusing on this point [13,14]. PCMs integrated in walls have already demonstrated potential benefits through multiple experimental studies [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies are focusing on this point [13,14]. PCMs integrated in walls have already demonstrated potential benefits through multiple experimental studies [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The experimental data demonstrated that PCM panels helped to decrease peak temperature, reduce temperature fluctuation and increase thermal inertia. Barreneche et al [85] investigated both thermal and acoustical characteristics of SSPCM layers in a building between 4th June 2013 and 4th September 2013. In the measurement, the indoor air temperature was decreased by 3°C for the room with PCMs.…”
Section: Experimental Studies For Building Wallsmentioning
confidence: 99%
“…This test was done on a fresh mix of low-strength materials by measuring the spread in two directions of a For hardened concrete properties, compression test was carried out. The test was conducted according to BS 1881: Part 116: 1983 [9]. According to ASTM C 796, at least three days before proceeding the testing, foamed concrete cube that will be conducted the compression test should be cured in a moist room with 100% relative humidity.…”
Section: Testing On Foamed Concretementioning
confidence: 99%